HOTS and LOTS-based assessment: The challenges faced by high school EFL teachers in assessing the students’ summative performance - Ivana Arlene Wellington; Ouda Teda Ena (Englisia: Journal of Language, Education, and Humanities, 2026)
Despite the Indonesian curriculum’s explicit emphasis on Higher-Order Thinking Skills (HOTS), senior high school EFL teachers continue to experience difficulties in achieving a balanced integration of HOTS and Lower-Order Thinking Skills (LOTS) within summative assessments. This study investigates the challenges encountered by senior high school EFL teachers in assessing both higher-order and lower-order thinking skills in such assessments. Employing a qualitative descriptive design, data were collected from five EFL teachers in Magelang, Central Java, through semi-structured interviews and document analysis of teacher-made tests. The findings reveal a structural imbalance in which multiple-choice items—predominantly measuring LOTS—prevail, whereas HOTS-focused tasks remain limited in scope and frequency. This imbalance is attributed to institutional policies, students’ linguistic proficiency, pandemic-induced learning gaps, and insufficient teacher training in assessment design. The study concludes that meaningful integration of HOTS is contingent upon alignment among curricular objectives, assessment formats, teacher preparedness, and student proficiency levels. Such alignment necessitates enhanced assessment literacy among teachers and the provision of comprehensive instructional scaffolding within the Indonesian EFL context.